Dogville: between Jerzy Grotowski's theateral aesthetics and the human impulse in Friderich Nietzsche (Revista NUPEART, 2026)
This study analyzes the cinematographic work "Dogville" (2003), by Danish director Lars von Trier, focusing on three main pillars: signs and the power relationship, human impulses and the connection with Jerzy Grotowski's poor theater (1986), based on the philosopher Friderich Nietzsche's studies on "good" and "evil". The Judeo-Christian signs present in the film establish a parallel with the "dark" facets of the characters, which are revealed throughout the plot. This approach directs the viewer to deeply reflect on the inherent duality of "good" and "evil" in both oneself and others.
Keywords: Dogville; Cinema; Theater